2020
DOI: 10.1002/ajmg.a.62037
|View full text |Cite
|
Sign up to set email alerts
|

TBX5‐encoded T‐box transcription factor 5 variant T223M is associated with long QT syndrome and pediatric sudden cardiac death

Abstract: Long QT syndrome (LQTS) is a genetic disease resulting in a prolonged QT interval on a resting electrocardiogram, predisposing affected individuals to polymorphic ventricular tachycardia and sudden death. Although a number of genes have been implicated in this disease, nearly one in four individuals exhibiting the LQTS phenotype are genotype‐negative. Whole‐exome sequencing identified a missense T223M variant in TBX5 that cosegregates with prolonged QT interval in a family with otherwise genotype‐negative LQTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Variants affecting transcriptional regulators influencing SCN5A expression have been recently linked to long QT syndrome. In particular, Markunas et al [350] described a TBX5 variant that co-segregated with prolonged QT interval in a family with otherwise genotype-negative LQTS and demonstrated that such variant impaired the transactivation capacity of this transcription factor. Nieto-Marín et al [351] reported two additional TBX5 variants that co-segregated with LQT and BrS patients and electrophysiologically impaired I Na currents in vitro.…”
Section: Long Qt Syndromementioning
confidence: 99%
“…Variants affecting transcriptional regulators influencing SCN5A expression have been recently linked to long QT syndrome. In particular, Markunas et al [350] described a TBX5 variant that co-segregated with prolonged QT interval in a family with otherwise genotype-negative LQTS and demonstrated that such variant impaired the transactivation capacity of this transcription factor. Nieto-Marín et al [351] reported two additional TBX5 variants that co-segregated with LQT and BrS patients and electrophysiologically impaired I Na currents in vitro.…”
Section: Long Qt Syndromementioning
confidence: 99%